Mystery behind the wall - Warner, Gertrude Chandler, 1890-1979.; Cunningham, David (New York : Scholastic, 1993)
The Boxcar Children now living with their grandfatherdiscove an old journal behind a wall in the guest room that leads them to a valuable coin collection.
Paperback.
480
Keywords: Mystery and detective stories